The interplay between household food security and wellbeing among small‑scale farmers in the context of rapid agrarian change in India - Patel, Kirit; Gartaula, Hom; Johnson, Derek; Karthikeyan, M. (BioMed Central, 2015)
Background: Small-scale agriculture, government entitlements, and livelihood opportunities offered by rapid economic growth shape the food security and wellbeing of people in rural India. This paper analyses this ongoing process of agrarian development from the perspective of three major approaches: the food availability approach, the entitlement and livelihood approach, and food sovereignty. We draw on quantitative and qualitative data collected from 68 households in rural Tamil Nadu on landholding and management, farm diversity, agricultural production, food availability, off-farm employment, rural out-migration, objective and subjective wellbeing, and socioeconomic and demographic profile of respondents. Results: Rural households were classified in four categories, based on their engagement in agriculture and off-farm employment, to understand the interplay between food sufficiency and wellbeing. The households solely based on small-scale agriculture were found to have higher food sufficiency, landholding, and crop diversity, but lower monthly income and wellbeing. The households that were engaged in off-farm employment in addition to agriculture were found to have lower food sufficiency, landholding, and crop diversity, yet they exhibited better wellbeing and higher income. The landless households, which were primarily engaged in off-farm labour, work in distant markets had higher income than households solely engaged in farming. However, they had the lowest wellbeing index among all household types. The findings indicated that the impacts of women’s participation in local or distant employment schemes on household food security and wellbeing were complex and shaped by the household’s engagement in agriculture and their aspirations for a better quality of life. Conclusions: None of the three food security approaches provides a fully satisfactory basis for interventions aimed at enhancing the capacity of small and marginal farmers to achieve food security and meet their aspirations for wellbeing in the research area, although the entitlements and livelihoods approach has had a significant impact on local possibilities for livelihoods diversification. The study demonstrates that the interaction between food security and the subjective wellbeing of farmers is complex and shaped by the productivity of small-scale agriculture and livelihood aspirations of farm households.
DOI 10.1186/s40066-015-0036-2
Keywords: Agrarian change; Food security; Social wellbeing; Food sovereignty; Tamil Nadu; India